An immigration history of Britain : multicultural racism since 1800 - Panayi, Panikos (Pearson Longman, 2010)
"Immigration, ethnicity, multiculturalism and racism are often perceived as recent additions to the British social and cultural landscape - yet, far from being new, these phenomena have characterised British life since the 19th century. Although the numbers of immigrants have increased since the Second World War, groups such as the Irish, Germans and East European Jews have been arriving, settling and making an impact on British society from the Victorian period onwards.